Multi-stage network-based two-type cost minimization for the reverse logistics management of inert construction waste - Ahmed, Rana Rabnawaz; Zhang, Xueqing (Waste management (Elmsford), 2021)
•Developed a multi-stage network-based cost minimization model.•Applied reverse logistics to inert construction waste management.•Considered facility-based costing and non-facility based costing.•Formulated a mixed-integer linear programming model.•Conducted a case study to demonstrate the application of the developed model.•Results indicating a 24% reduction in the total cost. The growing concerns for achieving sustainability has gained much attention from waste management experts with particular focus on reverse logistics, as it supports concepts like circular economy, material recovery, and improved environmental performances. This paper describes a multi-stage network-based model to minimize the overall cost for the reverse logistics management of inert construction waste across its entire life cycle. This model takes a unique two-type costing approach to overcome the ambiguities and deficiencies existing in previous models. Type-I cost refers to the facility-based costing (FBC) and Type-II cost refers to non-facility based costing (NFBC). The mixed-integer linear programming technique is applied using the LINGO software. A case study of construction waste management in Hong Kong is conducted to validate the developed model, which includes waste generation point as the starting node, public fill reception facility and recycling facility as an intermediate node, and landfill as an ending node. The result shows about 24% reduction in the total cost compared to the base case. Furthermore, to evaluate the impact of uncertainties on the cost parameters, a detailed scenario based sensitivity analysis is conducted. The optimal result shows that the larger portion of total cost come from the NFBC component. Therefore, NFBC is critical in defining the overall reverse logistics network and thus, should be given more emphasis in the design of an effective construction waste management system.